1992
DOI: 10.1152/physrev.1992.72.3.731
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal signals originating in the gonads

Abstract: The discovery of the various peptide factors in the gonads followed different paths. A number of factors were specifically searched for because of physiological experiments that predicted that an activity from the gonads was necessary to explain phenomena. Such was the case for gonadal steroids and for such peptide factors as inhibin, MIS, OMI, FRP, seminal plasma inhibin, relaxin, PA factor and other proteases, and ABP. In the process other factors such as activin and follistatin were serendipitously discover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(40 citation statements)
references
References 0 publications
1
38
0
1
Order By: Relevance
“…Although oocyte maturation is triggered by the GTH surge, GTH receptor expression was not detected in either the oocyte itself or its surrounding cumulus cells, but these receptors were expressed in the follicular cells of both theca and granulosa cells (Peng et al 1991). In this context, Ackland et al (1992) previously reported that some paracrine factors, which accumulate in follicular fluid in response to GTH, may affect oocyte maturation. Thus, we propose that these factors could be used in an IVM system, and would be expected to improve its efficiency.…”
Section: Discussionmentioning
confidence: 98%
“…Although oocyte maturation is triggered by the GTH surge, GTH receptor expression was not detected in either the oocyte itself or its surrounding cumulus cells, but these receptors were expressed in the follicular cells of both theca and granulosa cells (Peng et al 1991). In this context, Ackland et al (1992) previously reported that some paracrine factors, which accumulate in follicular fluid in response to GTH, may affect oocyte maturation. Thus, we propose that these factors could be used in an IVM system, and would be expected to improve its efficiency.…”
Section: Discussionmentioning
confidence: 98%
“…However, the present results show that in the progesterone-treated gonadectomized rats high levels of 20a-OHP do not correspond with increased cell proliferation. Next to steroids, the gonads of the male and the female produce and secrete appreciable amounts of all kinds of growth factors, such as activin and inhibin (16,17), members of the transforming growth factor-b superfamily of growth factors, which generally inhibit pancreatic cell replication (18,19), and the insulin-like growth factors-I and -II (20)(21)(22), which are capable of stimulating pancreatic islet-cell proliferation (23). Moreover, in human testis (24) and ovary (25) a growth hormone/placental lactogen variant is produced which also might stimulate cell proliferation in pancreatic tissue (cf.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid rise in serum FSH following gonadectomy in both sexes is due to removal of gonadal inhibin, the major negative regulator of FSH in mammals [25][26][27], Because pituitaries from intact females have been exposed to much higher in vivo inhibin levels than those of males [27], basal FSH release in vitro by pituitaries from intact females is much lower than that of male pituitaries. How ever, in vitro FSH secretion increases with time of basal perifusion by pituitaries from intact females, and is far greater by pituitaries from ovariectomized females, likely due to pituitary withdrawal from high serum inhibin lev els [14], In contrast, exposure to low in vivo levels of serum inhibin by male pituitaries means that male pitu itary FSH experiences less change in relative serum inhi bin levels following gonadectomy, and consequently there is less change in in vitro FSH release by pituitaries from gonadectomized males.…”
Section: Discussionmentioning
confidence: 99%